Early onset of APC/C activity renders SAC inefficient in mouse embryos - Horakova, Adela; Konecna, Marketa; Radonova, Lenka; Anger, Martin (Frontiers in Cell and Developmental Biology, 2024)
Control mechanisms of spindle assembly and chromosome segregaDon are vital for prevenDng aneuploidy during cell division. The mammalian germ cells and embryos are prone to chromosome segregaDon errors and resulDng aneuploidy is a major cause of terminaDon of development or severe developmental disorders. Here we focused on early mouse embryos, and using combinaDon of methods involving microinjecDon, immunodetecDon and confocal live cell imaging, we concentrated on the Spindle Assembly Checkpoint (SAC) and Anaphase PromoDng Complex/Cyclosome (APC/C). These are two important mechanisms cooperaDng during mitosis to ensure accurate chromosome segregaDon, and assessed their acDvity during the first two mitoses a[er ferDlizaDon. Our results showed, that in zygotes and 2-cell embryos, the SAC core protein Mad1 shows very low levels on kinetochores in comparison to oocytes and its interacDon with chromosomes is restricted to a short Dme interval a[er nuclear membrane disassembly (NEBD). Exposure of 2-cell embryos to low levels of spindle poison does not prevent anaphase, despite the spindle damage induced by the drug. And lastly, the APC/C is acDvated coincidentally with NEBD, before the spindle assembly compleDon. This early onset of APC/C acDvity, together with precocious relocalizaDon of Mad1 from chromosomes, prevents proper surveillance of spindle assembly by SAC. The results contribute to the understanding of the origin of aneuploidy in early embryos.